Structural Studies of Bacterioferritin B (BfrB) from Pseudomonas aeruginosa Suggest a Gating Mechanism for Iron Uptake via the Ferroxidase Center - Weeratunga, Saroja K. (2010)
The structure of recombinant P. aeruginosa bacterioferritin B (Pa BfrB) has been solved from crystals grown from protein devoid of core mineral iron (as-isolated) and from protein mineralized with ~ 600 iron atoms (mineralized). Structures were also obtained from crystals grown from mineralized BfrB after soaking them in FeSO(4) solution (Fe soak) and in separate experiments after soaking them in FeSO(4) solution followed by soaking in crystallization solution (double soak). Although the structures consist of a typical bacterioferritin fold comprised of a nearly spherical 24-mer assembly that binds 12 heme molecules, comparison of microenvironments observed in the distinct structures provided interesting insights: The ferroxidase center in the as-isolated, mineralized and double soak structures is empty. The ferroxidase ligands (except His130) are poised to bind iron with minimal conformational changes. The His130 side chain, on the other hand, must rotate toward the ferroxidase center to coordinate iron. In comparison, the structure obtained from crystals soaked in an FeSO(4) solution display a fully occupied ferroxidase center and iron bound to the internal, Fe((in)), and external, Fe((out)), surfaces of Pa BfrB. The conformation of His130 in this structure is rotated toward the ferroxidase center and coordinates an iron ion. The structures also revealed a pore on the surface of Pa BfrB that likely serves as an entry port for Fe(2+) to the ferroxidase center. On its opposite end the pore is capped by the side chain of His130 when it adopts its “gate closed” conformation that enables coordination to a ferroxidase iron. A change to its “gate-open”, non-coordinative conformation, creates a path for the translocation of iron from the ferroxidase center to the interior cavity. These structural observations, together with findings obtained from iron incorporation measurements in solution suggest that the ferroxidase pore is the dominant entry route for the uptake of iron by Pa BfrB. These findings, which are clearly distinct from those made with E. coli Bfr (Crow, A. C., Lawson, T. L., Lewin, A., Moore, G. R., and Le Brun, N. E. (2009) J. Am. Chem. Soc. 131, 6808–6813) indicate that not all bacterioferritins operate in the same manner.